2019
DOI: 10.1515/ijeeps-2018-0264
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Unit Commitment with Concentrated Solar Power and Thermal Energy Storage in Afghanistan Electrical System

Abstract: Power sector, as one of the least progressed division, is limiting the socioeconomic development in Afghanistan. Although the country has a vast solar energy potential with a bright prospect for growth, however inadequate endorsement and attention have prevented its proper use. Meanwhile, Kabul the capital city and one of the fastest growing cities in the world, is suffering severe challenges to supply its energy needs. Presently, Kabul electrical system is subjected to insecure and insufficient supply due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Such Gurobi (Jiang et al, 2022) and CPLEX (Zhou et al, 2022), which are widely used due to their superior performance. Some other solvers such as MOSEK (Zhang et al, 2018), XPRESS (Andrychowicz and Olek, 2016), LINGO (Xu et al, 2020b), INTLINPROG (Ibrahimi et al, 2019) are also commonly found in the literature. However, the core algorithms of these solvers are also based on classical algorithms or intelligent algorithms or hybrid algorithms of classic and intelligent.…”
Section: Model Solution Algorithms For Re-hes's Configurationmentioning
confidence: 99%
“…Such Gurobi (Jiang et al, 2022) and CPLEX (Zhou et al, 2022), which are widely used due to their superior performance. Some other solvers such as MOSEK (Zhang et al, 2018), XPRESS (Andrychowicz and Olek, 2016), LINGO (Xu et al, 2020b), INTLINPROG (Ibrahimi et al, 2019) are also commonly found in the literature. However, the core algorithms of these solvers are also based on classical algorithms or intelligent algorithms or hybrid algorithms of classic and intelligent.…”
Section: Model Solution Algorithms For Re-hes's Configurationmentioning
confidence: 99%
“…Therefore, sustainable operation recommends a broader perspective, balancing technical, technological, economic, environmental, institutional, social appraisals for optimum benefits for long-run sustainability [7]. Power systems reliability and stability of supply, security, flexibility, and proper operation owing optimum deployment of smart technologies and storage systems that make the possible increase in profitability, satisfaction in services delivery, and competitiveness in the market [8][9][10]. Managing supply and demand sides and propose a quick response to transient increases or decreases in power supply from alternating renewable sources, the different storage solutions may be hierarchies based on their ability, ensuring dynamic pricing structures are recommended [11].…”
Section: Energy Sustainabilitymentioning
confidence: 99%
“…Site selection as the first step has a significant impact on the cost, efficiency, and entire life of CSP plants. Multicriteria observance like availability of flat land, water resource, electricity network, and road expected to be considered for the relevant sites [32]. Based on the site selection requirements, the Direct Normal Irradiation (DNI) for the site of a CSP plant should be over 1800 kWh/m 2 /year (5.2 kWh/m 2 /day) [33].…”
Section: Potential Of Csp Technology In Afghanistanmentioning
confidence: 99%